The European carbon border adjustment mechanism: a small step in the right direction - Niko Korpar; Mario Larch; Roman Stöllinger (International Economics and Economic Policy, 2022)
We estimate the effects of a European Carbon Border Adjustment (CBA) mechanism on exports, real GDP, welfare and emissions using the multi-region, multi-sector structural gravity model of Larch and Wanner (55). Incorporating the main industries covered in the proposal of the European Commission from mid-2021, as well as its other design features, and assuming prevailing CO2 prices, we find only small effects of the European CBA mechanism. EU exports are estimated to decline by 0.04%, while CO2 emissions in EU countries increase by 0.24%. These negligible results mask larger adjustments at the sectoral level. The structural changes will shift the EU economy towards more emission-intensive industries, which will make achieving its climate goals harder. On the positive side, the European CBA mechanism will reduce global emissions by 0.08%. Given the minute economic costs in terms of GDP and welfare losses, the CBA mechanism seems an appropriate policy tool, though its proposed design will not be able to make a significant contribution to mitigating global climate change.
Keywords: F13; F14; F17; F18; Q56; 330; Carbon border taxes; Carbon tariffs; Carbon leakage; Climate change